2017
DOI: 10.1177/0310057x1704500216
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Audit to Assess the Efficacy of the Coolsense® Pain Numbing Applicator for Intravenous Cannulation in Children

Abstract: The Coolsense® device is a topical applicator that is used to anaesthetise the skin before a painful procedure. It is a handheld device with a temperature-controlled head that acts on application, without chemicals, to cool and anaesthetise the site of injection. This prospective observational audit of 100 children and adolescents aged six to 18 years studied the analgesic efficacy and patient and carer satisfaction rating of the device during intravenous cannulation and complications arising from its use. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…To the authors' knowledge, this is the first reported use of the CoolSense device in animals. Other reports have shown it to be effective before intravenous catheterisation in children, 4 as well as for procedures involving intradermal injections 5 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the authors' knowledge, this is the first reported use of the CoolSense device in animals. Other reports have shown it to be effective before intravenous catheterisation in children, 4 as well as for procedures involving intradermal injections 5 …”
Section: Discussionmentioning
confidence: 99%
“…Whilst planning a pharmacokinetic study requiring multiple, repeated percutaneous fine needle aspirations in sheep, we chose to test a commercially available analgesic device (CoolSense; Coolsense Ltd). Although the device has been shown to be effective in reducing needle‐stick pain in humans, 4,5 there was no reported evaluation of the CoolSense device in veterinary species.…”
mentioning
confidence: 99%
“…A prospective observational audit of 100 children aged 6 to 18 years found Coolsense to be safe and a useful tool during intravenous (IV) cannulation for minimising pain. 8 Coolsense is fully registered by the Therapeutics Goods Administration (2013) as a reusable, noninvasive hand-held device that immediately cools and numbs the skin at the site of an injection. 9 It has been used for providing topical anaesthesia for painful procedures of the skin such as IV cannulation, venous blood tests and blood glucose testing.…”
Section: What This Paper Addsmentioning
confidence: 99%
“…More recently another device, Coolsense has been trialled in the Royal Children's Hospital departments of Medical Imaging and Anaesthetic. A prospective observational audit of 100 children aged 6 to 18 years found Coolsense to be safe and a useful tool during intravenous (IV) cannulation for minimising pain 8 . Coolsense is fully registered by the Therapeutics Goods Administration (2013) as a reusable, noninvasive hand‐held device that immediately cools and numbs the skin at the site of an injection 9 .…”
mentioning
confidence: 99%
“…CoolSense is a handheld device approved by Food and Drug Administration and the European Commission as a topical skin-numbing applicator. 5 The device is placed in the freezer for 1 hour before use. The cooled metal head is sterilized with alcohol gel and then applied to the patient's skin for 4 to 5 seconds immediately prior to injection.…”
mentioning
confidence: 99%